Intelligent Negotiation Mechanism for Supporting the Interoperability within the Sensing Enterprise - Stanescu, A.; Cretan, A.; Coutinho, C.; Jardim-Goncalves, R. (IFAC Proceedings Volumes, 2013)
The Sensing Enterprise is a novel concept that refers to an enterprise anticipating future decisions by using multi-dimensional information captured through physical and virtual objects. The Sensing Enterprise concept is shifting focus towards a borderless enterprise, having at its core the collaboration and continuous interactions among smart objects and systems. But in the actual competitive and global business context, the maintenance of the collaboration environment through the interoperation among heterogeneous smart virtual and physical objects in a collaborative organizational environment becomes difficult to achieve. Therefore, in a dynamic context a change in any component of the networked partners affects the others, creating difficulties to sustain operating networked environment. In this respect, this paper proposes an intelligent negotiation framework as a key mechanism to achieve and maintain the interoperability between the organisations smart objects and applications, and its validation in an industrial scenario. To allow a sustainable, flexible and generic approach towards the infrastructure implementation in global scale, a cloud-based platform is proposed for setting of the Sensing Enterprise framework.